2002
DOI: 10.1080/09603100010001937
|View full text |Cite
|
Sign up to set email alerts
|

Financial liberalization and stock market volatility in selected developing countries

Abstract: This study empirically investigates whether stock market volatility increased following financial liberalization, in six 'emerging' markets. The sample countries are Argentina, India, Pakistan, Philippines, South Korea and Taiwan. To examine the issue, the news impact curves are utilized which relate current volatility to past news. The news impact curves are derived from the parameters of EGARCH models which measure the conditional volatility of stock returns in the sample markets. The results suggest that vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 8 publications
2
27
0
1
Order By: Relevance
“…The easy access to information by domestic and foreign companies associates positively to stock market development. Kassimatis (2002) conducts the research in six countries: Argentina, India, Pakistan, Philippines, South Korea and Taiwan, which confirms that openness of financial market reduces its volatility. Several recent empirical researches also present the positive relationship between financial integration and equity market development.…”
Section: Financial Liberalization and Stock Market Developmentmentioning
confidence: 54%
“…The easy access to information by domestic and foreign companies associates positively to stock market development. Kassimatis (2002) conducts the research in six countries: Argentina, India, Pakistan, Philippines, South Korea and Taiwan, which confirms that openness of financial market reduces its volatility. Several recent empirical researches also present the positive relationship between financial integration and equity market development.…”
Section: Financial Liberalization and Stock Market Developmentmentioning
confidence: 54%
“…Bekaert & Harvey (1997) demonstrated that in 13 of their 17 sample countries, liberalization of equity markets led to a substantial drop in volatility; this was especially significant in 5 emerging markets (Taiwan, Mexico, Portugal, Argentina, and Brazil), after controlling for potential factors influencing the time-varying volatility. Kassimatis (2002) demonstrated that volatility was reduced after relaxing financial markets in five out of six sample developing countries. The results were partly consistent with those of Bekaert & Harvey (1997).…”
Section: Liberalization In Emerging Marketsmentioning
confidence: 98%
“…Researchers also find stock market volatility transmission between friendly countries of different regions (e.g., Pakistan and China) having economic links [2]. They find evidence of reduced volatility after implementation of financial liberalization policies in Pakistan [3]. Some suggest that that stock trades' volume causes volatility [4,5] and an asymmetrical volatility is due to response between volume and price [6].…”
Section: Literature Reviewmentioning
confidence: 99%